Preparation method and application of high-performance nano calcium silicate hydrate seed crystal early strength agent

By optimizing the co-precipitation method, the particle size and morphology of nano-hydrated calcium silicate seeds are controlled by using water-in-oil microemulsion technology, which solves the problem of insufficient early strength of cement stones in the existing technology, and achieves efficient and stable early strength improvement of cement stones.

CN119774905APending Publication Date: 2025-04-08CHINA UNIV OF PETROLEUM (EAST CHINA)

Patent Information

Application Number
CN202510015803.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the early strength of cement stone under low temperature conditions, and it is difficult to control the particle size of the early strength agent, which affects its stability and performance.

Method used

By optimizing the co-precipitation method, a micro reactor is formed by isolating the aqueous phase with a water-in-oil microemulsion to control the particle size and morphology of nano-hydrated calcium silicate seeds, and a stable preparation of high-performance nano-hydrated calcium silicate seeds is achieved.

Benefits of technology

It significantly shortens the initial settling time of cement slurry, improves the early strength of cement stone, and has no adverse effects on the later strength, and has a stable particle size distribution, reducing the synthesis cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005229879910000171
    Figure BDA0005229879910000171
  • Figure BDA0005229879910000181
    Figure BDA0005229879910000181
  • Figure BDA0005229879910000191
    Figure BDA0005229879910000191
Patent Text Reader

Abstract

The invention discloses a method for preparing a nano calcium silicate hydrate seed crystal early strength agent by using a microemulsion and application of the nano calcium silicate hydrate seed crystal early strength agent. The preparation method comprises the following steps: preparing a water-in-oil microemulsion; the invention relates to a method for preparing a nano calcium silicate hydrate seed crystal early strength agent by taking a microemulsion as a dispersion phase and application. The microreactor is constructed by utilizing the characteristics of the microemulsion, and the reaction rate and the product size are controlled microcosmically and macroscopically, so that the product has better physical and chemical properties. According to the invention, the traditional microemulsion and the surfactant-free microemulsion are used, so that the problem of surfactant residue in the product is well solved, and the separation cost is reduced; and the oil phase solution after the precipitation product is separated can be recycled, so that the synthesis cost is further reduced. The obtained product has the characteristics of small particle size, stable particle size distribution and good dispersity, has a remarkable improvement effect on the early strength and the compactness of set cement, and does not reduce the later strength at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oil and gas well cementing and completion, and in particular to a preparation method and application of a high-performance nano calcium silicate hydrate seed early strength agent. Background Art

[0002] Cementing of oil and gas wells is to inject cement slurry between the annulus well wall and the casing, and then solidify to form a cement ring. The purpose is to isolate the oil, gas and water layers, prevent interlayer crosstalk, protect the casing, and increase the life of the oil and gas wells. It is one of the important links in drilling and completion engineering, and is also an important basis for subsequent completion and various oil production processes. With the gradual deepening of oil and gas field development, the increasingly complex geological conditions of the formation have gradually increased the requirements for cementing technology. In order to enable the cement ring to improve its early strength in a complex formation environment and meet the process requirements, it has become an inevitable trend to add high-performance materials to the cement base to improve its early performance. There are also many types of materials that have been used as cement additives.

[0003] At present, the early strength agents used to improve the mechanical properties of oil well cement mainly include chlorides, sulfates and organics. These early strength agents have a certain effect on improving the early compressive strength of cement paste. However, some studies have shown that chloride early strength agents will increase the yield value of cement slurry, increase permeability and reduce the ability to resist sulfate corrosion; sulfate early strength agents often have too fast a rate of early hydration product generation, making the structure not dense enough, which has an adverse effect on the later strength; the dosage of organic early strength agents is not easy to control, and excessive dosage will cause serious slow setting and strength reduction. Therefore, in order to improve the early strength of cement paste under low temperature conditions, it becomes a problem to study an efficient and stable early strength agent.

[0004] Nanomaterials have been a hot topic in recent years, and the use of seed nucleation is a new direction for improving the early strength of concrete. At present, nanomaterials such as nano-silica, nano-alumina, and nano-calcium carbonate have been proven to have excellent performance as cement additives. Among them, nano-calcium silicate hydrate (CSH) particles have the most significant effect on promoting hydration, and their combination with cement is more dense. Therefore, the addition of nano-CSH particles is expected to become a new technical approach to improve the early strength of cement. Because of its various synthesis methods and use environments, it has a deep research depth and breadth.

[0005] However, as CSH gel is the main product of cement hydration, it is difficult to separate pure CSH substances from the complex hydration process. With the deepening of research on nanomaterials, scholars have designed some methods for synthesizing CSH nanocrystals based on laboratory conditions and scale: (1) Single mineral hydration method: CSH is generated by reacting tricalcium silicate (C3S) or dicalcium silicate (C2S) with water. The calcium-silicon ratio and degree of polymerization of the product can be controlled by increasing the temperature and extending the hydration time; however, there are many CH phases in the product that are difficult to remove, and the product may be carbonized. The product particle size is also large, generally in the micron level. (2) Hydrothermal method: Nano-CSH is prepared by reacting volcanic ash under high temperature conditions (80-150℃). This method has the characteristics of fast reaction speed and the product is also nano-sized; however, the reaction is difficult to be completed, the product is a mixture, and it is difficult to solve the problem of product agglomeration. The equipment requirements are also high and it is difficult to carry out under laboratory conditions. (3) Sol-gel method: CSH is prepared by the polycondensation reaction of metal alkoxides and water. It has the advantages of high purity, high uniformity, and easy reaction control. However, it has high requirements for the reaction environment and experimental equipment, and the raw materials are expensive and have certain risks. Therefore, it is not a production method that is conducive to large-scale production. (4) Co-precipitation method: Using polymer as a template, CSH nanoparticles are synthesized by reacting soluble calcium salts with silicon source solutions. The reaction process can be controlled by adjusting pH, reaction time, temperature and other conditions. The product has a smaller particle size and dispersion. It is currently a common method for synthesizing nano-CSH.

[0006] For nano-calcium silicate hydrate used as an early strength agent, the following requirements are imposed on its physicochemical properties: (1) Particle size: Particle size is a direct factor affecting the early strength performance of nano-crystal seeds. The smaller the particle size of the nano-crystal seeds, the larger the specific surface area and the larger the contact area with the cement slurry, which is conducive to the early strength performance of the nano-crystal seeds. (2) Dispersion (dispersion ability): Better dispersion ability can effectively prevent the agglomeration of CSH nanoparticles in water, enable better contact with cement, exert early strength performance, make them free in the cement slurry system, and avoid a large amount of crystallization products covering the particle surface. The dispersion of nanoparticles is usually improved by surface modification. (3) Particle morphology: Particle morphology is also one of the factors affecting the early strength performance of nanoparticles. Depending on the preparation method, the morphology of the product will be different. It and the particle size of the nanoparticles jointly determine the early strength performance of a single particle. (4) Calcium-silicon ratio: The ratio of calcium-silicon molecules in the structure of CSH will affect its accelerating effect on cement hydration. As the calcium-silicon ratio increases, the average chain length of CSH gradually decreases, which will lead to a decrease in its specific surface area and affect the early strength performance of the nanoparticles.

[0007] Chinese patent document CN118420264A discloses a highly dispersed and stable nano calcium silicate hydrate seed early strength agent and its preparation method and application, which prepares nano calcium silicate hydrate particles by coprecipitation of calcium and silicon source solution, optimizes the polycarboxylic acid structure, and modifies it, and the product particle size is mainly distributed below 150nm. The method of increasing the concentration of calcium and silicon ions by titration will cause the seed to continue to grow, and it is difficult to control the particle size of the nanoparticle product.

[0008] Chinese patent document CN117209200A discloses a nano calcium silicate hydrate crystal nucleus early strength agent and its preparation, which comprises mixing a crystal nucleus growth inhibitor, an emulsifier and water to obtain an O / W emulsion; adding a calcium / silicon source solution to the obtained emulsion under stirring conditions, thereby obtaining a nano calcium silicate hydrate product, the particle size of which is mainly distributed in 100-150nm. The main function of the emulsion is to adjust the solubility of the crystal nucleus growth inhibitor, and the reaction is still carried out in a continuous aqueous phase, so it is difficult to control the progress of the reaction and the particle size of the product.

[0009] Chinese patent document CN116535219A discloses a preparation method and application of a nano calcium silicate hydrate type super early strength agent, in which the synthesis method and type of co-precipitation template polycarboxylic acid are optimized, thereby improving the performance of the modified nano calcium silicate hydrate type early strength agent, and the product particle size is 60-110nm. However, the specific method for synthesizing nano calcium silicate hydrate seeds is still the traditional co-precipitation method, which has the problem of continuous growth and agglomeration of the product in the dispersed phase.

[0010] Therefore, a method for efficiently and stably preparing high-performance nano-calcium silicate hydrate is of great significance for solving various problems in low-temperature cementing and the application research of nanomaterials in high-temperature deep cementing. Summary of the invention

[0011] The purpose of the present invention is to provide a method for efficiently and stably synthesizing high-performance nano calcium silicate hydrate seeds. The product nano calcium silicate hydrate seeds can effectively accelerate the hydration process of cement according to the effect of early strength of the seeds, and effectively solve the problems that small-particle CSH nano seeds are difficult to stably synthesize and the cement has a long initial setting time and insufficient early strength under low temperature conditions.

[0012] Compared with other synthesis methods, the present invention has the following advantages:

[0013] 1. Through the properties of oil-in-water microemulsion, the co-precipitation method is optimized, and the water phase is isolated to form a microreactor, which can better control the size and shape of the product particles and have a stable and concentrated particle size distribution. Depending on the preparation of the microemulsion, the product D50 particle size can be controlled to be stable at 50-100nm.

[0014] 2. By adjusting the pH value of the reaction system, synthesis temperature, type of emulsion, aging time, adding modifying substances, etc., the physical and chemical properties of the product that affect its early strength performance, such as particle size, dispersibility, particle morphology, calcium-silicon ratio, etc., can be controlled from many aspects.

[0015] 3. The present invention selects a hydrophobic deep eutectic solution as the oil phase solution to prepare a surfactant-free microemulsion, which has the property of responding to CO2, can simply separate the product by injecting CO2, and adjust the microscopic morphology of the product; and avoids the problem of surfactant residue.

[0016] 4. Furthermore, by applying the reversibility of the hydrophobic deep eutectic solution in response to CO2 properties and reducing the microemulsion by injecting nitrogen, the oil phase can be used multiple times to reduce the synthesis cost.

[0017] The specific preparation scheme of the nano-hydrated calcium silicate seed prepared by the present invention is as follows:

[0018] (1) Mixing the oil phase solution, source solution, surfactant and co-surfactant to prepare microemulsions A and B: Count by mass, mix the selected oil phase solution, surfactant, co-surfactant and source solution in a ratio of 20-40:10-35:4-8:10-35, stir at a speed of 500-800 r / min and heat to 50-70°C, stir for 30-60 min, and obtain a clear microemulsion; in this way, prepare microemulsions A and B with calcium and silicon source solutions as aqueous phases, respectively.

[0019] (2) The microemulsions A and B are quickly mixed, stirred at a speed of 500-800 r / min for 3-6 hours, and then aged for 12-24 hours. The aged microemulsion is centrifuged for 10 minutes at a speed of 4000 r / min. After centrifugation, the upper clear liquid is poured out, the lower oil phase is filtered, and then washed with acetone and ethanol three times to obtain a precipitated product; when a hydrophobic deep eutectic solution is used as the oil phase solution, CO2 can be introduced into the microemulsion after aging to separate the precipitated product.

[0020] (3) After washing the precipitated product, drying it at 70-85° C. for 1-2 days to obtain the nano calcium silicate hydrate seed early strength agent product, with a D50 particle size distribution of 50-100 nm.

[0021] The nano calcium silicate hydrate seed early strength agent is characterized in that the nano calcium silicate hydrate seed is added to cement ash at 1-6wt%, which can significantly shorten the initial setting time of cement slurry, improve the early strength of cement paste, and has no adverse effect on the later strength of cement paste.

[0022] The nano calcium silicate hydrate seeds are characterized in that the prepared nano calcium silicate hydrate seeds have a smaller particle size and can better exert the early strength performance of the seeds; and can be compatible with modification methods such as polycarboxylic acid to improve its dispersion performance, etc., and further enhance its early strength performance.

[0023] The nano calcium silicate hydrate seeds can be prepared using a surfactant-free microemulsion system, and a type of surfactant-free microemulsion is prepared using a hydrophobic deep eutectic solution as an oil phase solution: the hydrophobic deep eutectic solution and anhydrous ethanol are mixed in proportion, and the source solution is slowly titrated therein under stirring conditions at a speed of 500-800 r / min, the titration time is 1-2 hours, and the mass is counted, wherein the ratio of the hydrophobic deep eutectic solution, anhydrous ethanol, and the source solution is 30-50:10-20:10-40; the hydrophobic deep eutectic solution is measured in moles, and 4-methoxyphenol (HBD) and DMCHA (HBA) are mixed in a ratio of 1:1 and stirred at 25°C for 30 minutes to obtain the obtained product.

[0024] The nano-hydrated calcium silicate seeds of the present invention have good early strength performance under low temperature or room temperature environment. The strength of the test cement block is improved by 230% to 340% compared with the blank sample under the condition of curing for 8 hours, 100% to 180% under the condition of 12 hours, and 20% to 40% under the condition of 24 hours. After curing for 3 days and 7 days, there is still an improvement effect of more than 10%.

[0025] The nanometer calcium silicate hydrate seed crystal of the present invention uses physical centrifugation to separate the conventional oil phase solution in the synthesis and separation process, and the separated oil phase solution can be reused with a recovery rate of more than 75%. When a hydrophobic deep eutectic solution is used, the product surfactant removal step is avoided, and the hydrophobicity can be restored in a nitrogen environment of 65°C for recovery after the precipitation product and the supernatant are separated, and the recovery rate is more than 85%, which greatly reduces the synthesis cost.

[0026] The advantages of the present invention are:

[0027] (1) The nano-hydrated calcium silicate seed early strength agent of the present invention has a relatively small average particle size and a stable particle size distribution, and the particle size D50 of the seed is controlled within the range of 50 to 100 nm.

[0028] (2) The nano-hydrated calcium silicate seed early strength agent of the present invention can control the physicochemical properties of the seed such as the particle size, dispersibility, micromorphology and calcium-silicon ratio that affect the early strength ability of the seed by simply controlling the solution concentration and the synthesis conditions, and can give full play to the early strength effect of the seed and has excellent performance.

[0029] (3) The preparation method of the present invention can modify the nano calcium silicate hydrate seed early strength agent product by adding a modifying substance, so that it has better early strength performance.

[0030] (4) The CO2-responsive hydrophobic deep eutectic solution oil phase solution preferred in the present invention can use CO2 to separate the precipitated product, eliminating the step of separating the precipitated product with the surfactant, and after separation, the oil phase solution can restore its hydrophobicity and be recycled under a nitrogen environment at 65°C, with a recovery rate of more than 85%, which can effectively reduce the synthesis cost. DETAILED DESCRIPTION

[0031] The present invention is further described below by specific embodiments, but is not limited thereto. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the protection scope of the present invention.

[0032] The invention provides a method for preparing a nanometer calcium silicate hydrate seed early strength agent by using a water-in-oil microemulsion.

[0033] In the present invention, the formula of the microemulsion is not specifically specified and can be selected by a person skilled in the art.

[0034] Experimental methods used in technical effects: Preparation of cement slurry and compressive strength test of cement stone are carried out according to standard GB / T19139-2012 oil well cement test method.

[0035] The “parts” described in the embodiments and test examples are by default “parts by mass”, and “parts by mole” is particularly used and indicated when used.

[0036] The raw materials used in the examples are all conventional commercially available products. Jiahua G-grade cement is selected as oil well cement, and the cement composition is shown in Table 1.

[0037] Table 1 Chemical mineral composition of Jiahua G grade cement (wt.%)

[0038] <![CDATA[C3S]]> <![CDATA[C2S]]> <![CDATA[C3A]]> <![CDATA[C4AF]]> Dihydrate gypsum Hemihydrate gypsum Anhydrous gypsum 53.76 23.28 2.28 14.00 0.79 0.87 1.13

[0039] Example 1

[0040] This embodiment is intended to illustrate the nano-hydrated calcium silicate seeds prepared by the method of the present invention.

[0041] 35 parts of cyclohexane, 10 parts of OP-10, 4 parts of n-butanol and 10 parts of 4 mol / L calcium nitrate solution were weighed in a container in sequence, the temperature was raised to 60°C and stirred at a speed of 550 r / min for 45 min, and then cooled to room temperature to obtain microemulsion A; 35 parts of cyclohexane, 10 parts of OP-10, 4 parts of n-butanol and 10 parts of 4 mol / L sodium silicate solution were mixed in the same way to obtain microemulsion B; microemulsions A and B were quickly mixed, stirred at a speed of 550 r / min for 4 h, and aged for 12 h after the reaction was completed; after the aging was completed, the aged microemulsion was centrifuged, the time was set to 10 min, the speed was 4000 r / min, the supernatant was discarded after centrifugation, the lower oil phase was filtered, and then washed with acetone and ethanol for 3 times to obtain a precipitated product; the precipitated product was dried at 70°C for 1.5 d to obtain nano-hydrated calcium silicate seeds, recorded as S1.

[0042] Example 2

[0043] This embodiment is intended to illustrate the nano-hydrated calcium silicate seeds prepared by the method of the present invention.

[0044] 35 parts of cyclohexane, 10 parts of OP-10, 4 parts of n-butanol and 20 parts of 3.5 mol / L calcium nitrate solution were weighed in a container in sequence, heated to 60°C and stirred at 550 r / min for 45 min, and cooled to room temperature after heating and stirring to obtain microemulsion A; 35 parts of cyclohexane, 10 parts of OP-10, 4 parts of n-butanol and 20 parts of 3.5 mol / L sodium silicate solution were mixed in the same way to obtain microemulsion B; microemulsions A and B were quickly mixed, stirred at 550 r / min for 4 h, and aged for 12 h after the reaction was completed; after aging, the aged microemulsion was centrifuged, the time was set to 10 min, the speed was 4000 r / min, the supernatant was discarded after centrifugation, the lower oil phase was filtered, and then washed with acetone and ethanol for 3 times to obtain a precipitated product; the precipitated product was dried at 70°C for 1.5 d to obtain nano-hydrated calcium silicate seeds, recorded as S2.

[0045] Example 3

[0046] This embodiment is intended to illustrate the nano-hydrated calcium silicate seeds prepared by the method of the present invention.

[0047] 35 parts of cyclohexane, 10 parts of OP-10, 4 parts of n-butanol and 35 parts of 3 mol / L calcium nitrate solution were weighed in a container in sequence, the temperature was raised to 60°C and stirred at a speed of 550 r / min for 45 min, and then cooled to room temperature to obtain microemulsion A; 35 parts of cyclohexane, 10 parts of OP-10, 4 parts of n-butanol and 35 parts of 3 mol / L sodium silicate solution were mixed in the same way to obtain microemulsion B; microemulsions A and B were quickly mixed, stirred at a speed of 550 r / min for 5 h, and aged for 12 h after the reaction was completed; after the aging was completed, the aged microemulsion was centrifuged, the time was set to 10 min, the speed was 4000 r / min, the supernatant was discarded after centrifugation, the lower oil phase was filtered, and then washed with acetone and ethanol for 3 times to obtain a precipitated product; the precipitated product was dried at 70°C for 1.5 d to obtain nano-hydrated calcium silicate seeds, recorded as S3.

[0048] Example 4

[0049] This embodiment is intended to illustrate the nano-hydrated calcium silicate seeds prepared by the method of the present invention.

[0050] 35 parts of cyclohexane, 20 parts of OP-10, 6 parts of n-butanol and 20 parts of 3.5 mol / L calcium nitrate solution were weighed in a container in sequence, heated to 60°C and stirred at 550 r / min for 45 min, and cooled to room temperature after heating and stirring to obtain microemulsion A; 35 parts of cyclohexane, 20 parts of OP-10, 6 parts of n-butanol and 20 parts of 3.5 mol / L sodium silicate solution were mixed in the same way to obtain microemulsion B; microemulsions A and B were quickly mixed, stirred at 550 r / min for 5 h, and aged for 12 h after the reaction was completed; after the aging was completed, the aged microemulsion was centrifuged, the time was set to 10 min, the speed was 4000 r / min, the supernatant was discarded after centrifugation, the lower oil phase was filtered, and then washed with acetone and ethanol for 3 times to obtain a precipitated product; the precipitated product was dried at 70°C for 1.5 d to obtain nano-hydrated calcium silicate seeds, recorded as S4.

[0051] Example 5

[0052] This embodiment is intended to illustrate the nano-hydrated calcium silicate seeds prepared by the method of the present invention.

[0053] 35 parts of cyclohexane, 20 parts of OP-10, 6 parts of n-butanol and 10 parts of 4 mol / L calcium nitrate solution were weighed in a container in sequence, the temperature was raised to 60°C and stirred at a speed of 550 r / min for 45 min, and then cooled to room temperature to obtain microemulsion A; 35 parts of cyclohexane, 20 parts of OP-10, 6 parts of n-butanol and 10 parts of 4 mol / L sodium silicate solution were mixed in the same way to obtain microemulsion B; microemulsions A and B were quickly mixed, stirred at a speed of 550 r / min for 5 h, and aged for 12 h after the reaction was completed; after the aging was completed, the aged microemulsion was centrifuged, the time was set to 10 min, the speed was 4000 r / min, the supernatant was discarded after centrifugation, the lower oil phase was filtered, and then washed with acetone and ethanol for 3 times to obtain a precipitated product; the precipitated product was dried at 70°C for 1.5 d to obtain nano-hydrated calcium silicate seeds, recorded as S5.

[0054] Example 6

[0055] This embodiment is intended to illustrate the nano-hydrated calcium silicate seeds prepared by the method of the present invention.

[0056] Weigh 35 parts of n-conane, 20 parts of Brij-58, 6 parts of CTAB and 20 parts of 3 mol / L calcium nitrate solution in a container, heat to 70°C and stir at 550 r / min for 45 min, cool to room temperature after heating and stirring to obtain microemulsion A; mix 35 parts of n-conane, 20 parts of Brij-58, 6 parts of CTAB and 20 parts of 3 mol / L sodium silicate solution in the same way to obtain microemulsion B; quickly mix microemulsions A and B, stir at 550 r / min for 4 hours, and age for 12 hours after the reaction is completed; after aging, centrifuge the aged microemulsion, set the time to 10 min, and the speed to 4000 r / min. After centrifugation, pour off the upper clear liquid, filter the lower oil phase, and wash it with acetone and ethanol three times to obtain a precipitated product; dry the precipitated product at 70°C for 1.5 days to obtain nano-hydrated calcium silicate seeds, recorded as S6.

[0057] Example 7

[0058] This embodiment is intended to illustrate the nano-hydrated calcium silicate seeds prepared by the method of the present invention.

[0059] 35 parts of cyclohexane, 10 parts of Brij-58, 10 parts of OP-10, 6 parts of CTAB and 20 parts of 3 mol / L calcium nitrate solution were weighed in a container, heated to 60°C and stirred at 550 r / min for 45 min. After heating and stirring, it was cooled to room temperature to obtain microemulsion A. 35 parts of n-conane, 10 parts of Brij-58, 10 parts of OP-10, 6 parts of CTAB and 20 parts of 3 mol / L silica were mixed in the same way. sodium sulfate solution to obtain microemulsion B; quickly mix microemulsions A and B, stir and react at a speed of 550r / min for 4h, and age for 12h after the reaction is completed; after the aging is completed, centrifuge the aged microemulsion, set the time to 10min, and the speed to 4000r / min, pour out the upper clear liquid after centrifugation, filter the lower oil phase, and wash it with acetone and ethanol for 3 times to obtain a precipitated product; dry the precipitated product at 70℃ for 1.5d to obtain nano calcium silicate hydrate seeds, recorded as S7.

[0060] Example 8

[0061] This embodiment is intended to illustrate the nano-hydrated calcium silicate seeds prepared by the method of the present invention.

[0062] In terms of molar number, 4-methoxyphenol (HBD) and DMCHA (HBA) were mixed in a ratio of 1:1 and stirred at 25°C for 30 min to obtain a hydrophobic deep eutectic solution; in terms of mass number, 50 parts of a hydrophobic deep eutectic solution, 20 parts of anhydrous ethanol, and 35 parts of a 4 mol / L calcium nitrate solution were weighed in a container, heated to 65°C and stirred at a speed of 550 r / min for 1.5 h. After heating and stirring, the mixture was cooled to room temperature to obtain a microemulsion A; 50 parts of a hydrophobic deep eutectic solution were mixed in the same manner. The eutectic solution, 20 parts of anhydrous ethanol, and 35 parts of a sodium silicate solution with a concentration of 4 mol / L were prepared to obtain a microemulsion B; the microemulsions A and B were quickly mixed, stirred at a speed of 550 r / min for 4 hours, and aged for 12 hours after the reaction was completed; after the aging was completed, CO2 was introduced into the aged microemulsion until obvious stratification appeared, the upper clear liquid was separated, the lower oil phase was filtered, and then washed with acetone and ethanol for 3 times to obtain a precipitated product; the precipitated product was dried at 70°C for 1.5 days to obtain nano-hydrated calcium silicate seeds, recorded as S8.

[0063] Example 9

[0064] This embodiment is intended to illustrate the nano-hydrated calcium silicate seeds prepared by the method of the present invention.

[0065] 35 parts of cyclohexane, 10 parts of OP-10, 4 parts of n-butanol, 0.5 parts of polycarboxylic acid and 10 parts of 4 mol / L calcium nitrate solution were weighed in a container in sequence, heated to 60°C and stirred at 550 r / min for 45 min, and cooled to room temperature after heating and stirring to obtain microemulsion A; 35 parts of cyclohexane, 10 parts of OP-10, 4 parts of n-butanol, 0.5 parts of polycarboxylic acid and 10 parts of 4 mol / L sodium silicate solution were mixed in the same way to obtain microemulsion B; microemulsions A and B were quickly mixed, stirred at 550 r / min for 4 h, and aged for 12 h after the reaction was completed; after the aging was completed, the aged microemulsion was centrifuged, the time was set to 10 min, the speed was 4000 r / min, the supernatant was discarded after centrifugation, the lower oil phase was filtered and washed with acetone and ethanol for 3 times to obtain a precipitated product; the precipitated product was dried at 70°C for 1.5 d to obtain nano-hydrated calcium silicate seeds, recorded as S9.

[0066] Comparative Example 1

[0067] Prepare nanocrystalline seeds according to the same ratio as in Example 1

[0068] The difference is that the nanocrystal seeds are prepared by using a simultaneous titration method to prepare the microemulsion.

[0069] 70 parts of cyclohexane, 20 parts of OP-10 and 8 parts of n-butanol were weighed in a container in sequence, the temperature was raised to 60°C and stirred at 550 r / min for 30 min to obtain an oil phase solution; while the oil phase solution was stirred at 600 r / min, 10 parts of a 3 mol / L calcium nitrate solution and a sodium silicate solution were added dropwise at a speed of 1 ml / s, and stirring was continued for 3 h after the addition was completed; after the reaction was completed, the mixture was aged for 12 h; after the aging was completed, the aged microemulsion was centrifuged, the time was set to 10 min, the speed was 4000 r / min, the upper clear liquid was poured out after centrifugation, the lower oil phase was filtered, and then washed with acetone and ethanol for 3 times to obtain a precipitated product; the precipitated product was dried at 70°C for 1.5 d to obtain nano-hydrated calcium silicate seeds, recorded as DS1.

[0070] Comparative Example 2

[0071] Nanocrystalline seeds were prepared in the same manner as in Example 1.

[0072] The difference is that there is no heating or cooling during the preparation of nanocrystal seeds.

[0073] 35 parts of cyclohexane, 10 parts of OP-10, 4 parts of n-butanol and 10 parts of 4 mol / L calcium nitrate solution were weighed in a container in sequence, and stirred at a speed of 550 r / min for 45 min to obtain microemulsion A; 35 parts of cyclohexane, 10 parts of OP-10, 4 parts of n-butanol and 10 parts of 4 mol / L sodium silicate solution were mixed in the same way to obtain microemulsion B; microemulsions A and B were quickly mixed, stirred at a speed of 550 r / min for 4 h, and aged for 12 h after the reaction was completed; after the aging was completed, the aged microemulsion was centrifuged, the time was set to 10 min, the speed was 4000 r / min, the supernatant was discarded after centrifugation, the lower oil phase was filtered, and then washed with acetone and ethanol for 3 times to obtain a precipitated product; the precipitated product was dried at 70°C for 1.5 d to obtain nano-hydrated calcium silicate seeds, recorded as DS2.

[0074] Comparative Example 3

[0075] Nanocrystalline seeds were prepared in the same manner as in Example 1.

[0076] The difference is that the nanocrystal seed preparation process uses recycled oil phase

[0077] Weigh 35 parts of the recovered oil phase and 10 parts of a 4 mol / L calcium nitrate solution in a container, heat to 60°C and stir at 550 r / min for 45 min, cool to room temperature after heating and stirring to obtain microemulsion A; mix 35 parts of the recovered oil phase with 10 parts of a 4 mol / L sodium silicate solution in the same way to obtain microemulsion B; quickly mix microemulsions A and B, stir at 550 r / min for 4 h, and age for 12 h after the reaction is completed; after aging, centrifuge the aged microemulsion, set the time to 10 min, and the speed to 4000 r / min. After centrifugation, pour off the upper clear liquid, filter the lower oil phase, and wash with acetone and ethanol three times to obtain a precipitated product; dry the precipitated product at 70°C for 1.5 d to obtain nano-hydrated calcium silicate seeds, recorded as DS3.

[0078] Comparative Example 4

[0079] Nanocrystalline seeds were prepared in the same manner as in Example 1.

[0080] The difference is that the aging time is controlled during the preparation of nanocrystalline seeds.

[0081] 35 parts of cyclohexane, 10 parts of OP-10, 4 parts of n-butanol and 10 parts of 4 mol / L calcium nitrate solution were weighed in a container, heated to 60°C and stirred at 550 r / min for 45 min. After heating and stirring, the mixture was cooled to room temperature to obtain microemulsion A. 35 parts of cyclohexane, 10 parts of OP-10, 4 parts of n-butanol and 10 parts of 4 mol / L sodium silicate solution were mixed in the same way to obtain microemulsion B. Microemulsion A and B were quickly mixed to obtain microemulsion B. The reaction was stirred at a speed of 550 r / min for 4 hours. After the reaction was completed, the microemulsion was aged for 0, 24, and 48 hours. After the aging was completed, the aged microemulsion was centrifuged, and the time was set to 10 min at a speed of 4000 r / min. After centrifugation, the upper clear liquid was poured out, and the lower oil phase was filtered and washed with acetone and ethanol three times to obtain a precipitated product. The precipitated product was dried at 70°C for 1.5 days to obtain nano-hydrated calcium silicate seeds, which were recorded as DS4-1, DS4-2, and DS4-3, respectively.

[0082] Comparative Example 5

[0083] Nanocrystalline seeds were prepared in the same manner as in Example 1.

[0084] The difference is: add dilute hydrochloric acid to the source solution to adjust the pH to 7 ± 0.4

[0085] 35 parts of cyclohexane, 10 parts of OP-10, 4 parts of n-butanol and 10 parts of 4 mol / L calcium nitrate solution were weighed in a container, diluted hydrochloric acid was added to adjust the pH to 7±0.4, the temperature was raised to 60°C and stirred at a speed of 550 r / min for 45 min, and after the heating and stirring were completed, the mixture was cooled to room temperature to obtain microemulsion A; 35 parts of cyclohexane, 10 parts of OP-10, 4 parts of n-butanol and 10 parts of 4 mol / L sodium silicate solution were mixed in the same way to obtain microemulsion B; microemulsions A and B were quickly mixed, stirred at a speed of 550 r / min for 4 hours, and aged for 12 hours after the reaction was completed; after the aging was completed, the aged microemulsion was centrifuged, the time was set to 10 minutes, the speed was 4000 r / min, the supernatant was discarded after centrifugation, the lower oil phase was filtered, and then washed with acetone and ethanol for 3 times to obtain a precipitated product; the precipitated product was dried at 70°C for 1.5 days to obtain nano-hydrated calcium silicate seeds, which were recorded as DS5.

[0086] Test Example 1: Nanocrystalline seed product particle size and particle size distribution range test

[0087] The particle sizes of the nanocrystalline seed products prepared in Examples 1 to 9 and Comparative Examples 1 to 4 were respectively tested by Bettersize 2000 laser particle size analyzer.

[0088] The test results are shown in Table 2, which shows that the nanocrystalline seeds prepared by the present invention have a good average particle size and a stable particle size distribution range; the distribution range is the area where 80% of the product is located.

[0089] Table 2 Nanocrystalline seed product particle size

[0090] serial number Test samples Particle size range / nm D50 particle size / nm 1 S1 54.0~96.3 72.1 2 S2 62.8~103.4 80.0 3 S3 76.9~136.7 97.8 4 S4 59.7~92.6 77.1 5 S5 42.6~77.3 65.3 6 S6 47.8~80.3 67.1 7 S7 52.7~82.4 69.5 8 S8 53.6~77.9 62.4 9 S9 40.7~73.2 55.6 10 DS1 51.2~103.6 79.3 11 DS2 50.4~122.9 97.2 12 DS3 54.9~98.5 74.3

[0091] Test Example 2: Test on the influence of nano-seed on cement paste strength

[0092] According to GBT19139-2012 oil well cement test standard, cement slurry with a water-cement ratio of 0.44 was prepared, 100 parts of oil well cement and 44 parts of tap water were mixed, and the cement paste was cured and the compressive strength was tested; the compressive strength of the cement paste prepared by adding different parts of nanocrystalline seeds of Examples 1 to 9 and Comparative Examples 1 to 5 at 20°C and 60°C and different curing times was tested.

[0093] The test results are shown in Table 3. It can be seen that the present invention has an enhancement effect of 20% to 280% on the early strength of cement paste based on the seed early strength principle, and can effectively improve the early strength of cement paste by adding a small amount. This effect is particularly obvious in the early stage of cement hydration (within 24 hours), and only plays a densifying role after the hydration is basically completed (after 48 hours).

[0094] Combining Table 2 and Table 3, it can be seen that the early strength performance of the seed crystal is roughly inversely proportional to the average particle size; in Examples 1 to 7, the particle size of the microemulsion internal phase is adjusted by adjusting the oil-water ratio, the agent-water ratio, and the surfactant and co-surfactant components, thereby controlling the particle size of the product nano seed crystal and the early strength effect; in Example 8, a surfactant-free microemulsion system with a good internal phase particle size of a hydrophobic deep eutectic solution is preferably selected to obtain a nano seed crystal product with a smaller particle size and better early strength effect; in Example 9, a modifying material (PCE) is added to modify the nano seed crystal product to improve its dispersibility and polarity, which can also effectively reduce the particle size and enhance the early strength effect.

[0095] In addition, in Comparative Example 1, the nano seed product is synthesized by another more convenient method of forming a microemulsion, and the early strength performance is not significantly affected by other products with similar particle sizes; in Comparative Example 2, the morphological characteristics of the product nano seeds are changed to a certain extent by controlling the synthesis temperature, thereby showing different early strength performance under the same particle size; in Comparative Example 3, the recycled oil phase solution is used, which has no obvious effect on the seed particle size and early strength performance; in Comparative Example 4, the aging time is controlled to control the development of nano seeds, thereby obtaining seeds with different morphologies and particle sizes; in Comparative Example 5, the internal phase pH value is controlled to obtain nano seeds with different morphologies in a high pH environment.

[0096] Table 3 Effect of nano-seed on cement paste strength

[0097]

[0098]

[0099]

[0100] Test Example 3: Test on the effect of nano-seeds on early strength of cement paste under different conditions

[0101] According to GBT19139-2012 oil well cement test standard, a cement slurry with a water-cement ratio of 0.44 was prepared by mixing 100 parts of oil well cement with 44 parts of tap water, curing and testing the compressive strength of cement paste; additional tests were conducted by adding 5 parts of cement paste at different temperatures and different curing times.

[0102] The compressive strength of cement paste prepared by the nano-seeds of Examples 1 to 9 and Comparative Examples 1 to 5.

[0103] Compared with Test Example 2, this test example supplements the testing of the early strength effect of the present invention under other temperature environments (10, 30, 40°C) and shorter curing time (8h), further illustrating the scope of application and use effect of the present invention.

[0104] The test results are shown in Table 4. After adding a certain amount of product nano-seeds, the cement hydration rate is significantly increased and the early strength of cement paste is significantly enhanced. This early strength effect is particularly obvious in a low temperature environment. It can be seen that the present invention is suitable for a low temperature-normal temperature environment of 10 to 60°C, and can meet the requirements of on-site cementing for the early strength of cement paste.

[0105] Table 4 Effect of nano-seed on cement paste strength under different conditions

[0106]

[0107]

[0108]

[0109]

[0110] Test Example 4: Test on the effect of nano-seed on cement paste permeability

[0111] According to GBT19139-2012 oil well cement test standard, cement slurry with a water-cement ratio of 0.44 was prepared, 100 parts of oil well cement was mixed with 44 parts of tap water, and the porosity and permeability were tested using the mercury injection method for curing; 3 parts of nanocrystalline seeds of Examples 1 to 9 and Comparative Examples 1 to 3 were added respectively for the test, and the mixture was cured at a constant temperature of 25°C for 24 hours. The other experimental conditions refer to Test Example 2.

[0112] The test results are shown in Table 5. It can be seen that the permeability of the cement paste added with the present invention is significantly reduced, indicating that the present invention can effectively fill the gaps in the cement paste, increase the density of the cement paste, reduce the permeability of the cement paste, and improve the quality of the cement paste.

[0113] Table 5 Effect of nano-seed on cement paste permeability

[0114] serial number additive Porosity / % Permeability / mD 1 none 19.3 <![CDATA[1.92×10 -3 ]]> 2 S1 12.0 <![CDATA[1.13×10 -3 ]]> 3 S2 14.3 <![CDATA[1.32×10 -3 ]]> 4 S3 15.6 <![CDATA[1.44×10 -3 ]]> 5 S4 12.7 <![CDATA[1.19×10 -3 ]]> 6 S5 10.5 <![CDATA[1.20×10 -3 ]]> 7 S6 11.0 <![CDATA[1.27×10 -3 ]]> 8 S7 11.6 <![CDATA[1.33×10 -3 ]]> 9 S8 10.3 <![CDATA[1.10×10 -3 ]]> 10 S9 10.1 <![CDATA[1.27×10 -3 ]]> 11 DS1 12.4 <![CDATA[1.28×10 -3 ]]> 12 DS2 14.6 <![CDATA[1.38×10 -3 ]]> 13 DS3 12.9 <![CDATA[1.22×10 -3 ]]>

[0115] Test Example 5: Test on the influence of aging time on the physical and chemical properties of nanocrystalline seeds

[0116] The particle sizes of Example 1 and Comparative Examples DS5-1, DS5-2, and DS5-3 were respectively tested by Bettersize 2000 laser particle size analyzer.

[0117] The test results are shown in Table 6. Compared with the product S1 of Example 1, the unaged comparative example DS4-1 has incomplete seed development, a smaller particle size, but a smaller specific surface area, and poor early strength and filling effects; the comparative examples DS4-2 and DS4-3 aged for 24h and 48h have complete or overdeveloped seed development, resulting in slight agglomeration, which is not conducive to seed dispersion and has a certain impact on the early strength effect of the seed. In addition, the seed has different development speeds under different salt concentrations, stirring speeds, temperatures and other conditions, and the optimal aging time depends on the actual situation.

[0118] Table 6 Effect of aging time on the physical and chemical properties of nanocrystalline seeds

[0119]

[0120] Test Example 6: Test on the effect of nano-seeds on the initial and final setting time of cement slurry

[0121] According to GBT19139-2012 oil well cement test standard, a cement slurry with a water-cement ratio of 0.44 was prepared, and 5 parts of nano-seed early strength agent, 100 parts of oil well cement and 44 parts of tap water were mixed. The initial and final setting times of Examples 1 to 9, Comparative Examples 1 to 5 and the blank sample at 20°C and 40°C were compared.

[0122] The test results are shown in Table 7. Compared with the blank cement slurry, the initial setting time of the cement slurry with the addition of nano-seed products is shortened to varying degrees. The nano-seeds increase the contact area between cement particles and water phase through the early strength of the seeds, provide more nucleation sites for cement hydration, shorten the hydration induction period of cement, and achieve the effect of promoting cement hydration and shortening the initial and final setting times of cement.

[0123] In addition, the product of the embodiment has a smaller average particle size, a larger specific surface area, and a better hydration-promoting effect at the same addition amount; in comparative example 5, the pH value of the source solution is reduced, which makes the seed product more spherical, and the specific surface area is reduced compared with the tinfoil-like product at a high pH value, which is not conducive to the hydration-promoting effect of the nano-seed; the product S9 of example 9 is PCE-modified, and the surface of the nanoparticles is more non-polar, which is conducive to the dispersion of the nanoparticles in the cement slurry;

[0124] Table 7 Effect of nano-seeds on initial and final setting time of cement slurry

[0125]

[0126]

[0127] In summary, the present invention provides a preparation method and application of high-performance hydrated calcium silicate seeds, which can effectively synthesize hydrated calcium silicate nanoseeds with strong early strength properties, significantly improve the mechanical strength of cement stone, promote hydration, shorten the solidification time, and effectively meet the construction needs under low-temperature-normal temperature environments.

[0128] The above is only a preferred specific implementation of the present invention, but the present invention is not limited to the examples listed. Similar effects can be obtained in other embodiments by using the relevant materials and the method mechanism in the present invention. Therefore, for those skilled in the art, without departing from the principles and spirit of the present invention, the improvements made are all within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a high-performance nano-hydrated calcium silicate seed early strength agent, characterized in that: The preparation uses a microemulsion as a microreactor to coprecipitate and synthesize nanocrystalline seeds, and the particle size is well controlled, so that the product has high performance characteristics. The preparation of the nano-hydrated calcium silicate seeds includes the following steps: (1) mixing an oil phase solution, a source solution, a surfactant and a co-surfactant to prepare microemulsions A and B; (2) rapidly mixing microemulsions A and B, stirring the mixture at a speed of 500 to 800 r / min for 3 to 6 hours, aging the mixture for 12 to 24 hours, and separating the solid product; (3) washing the precipitated product and drying it in a ventilated environment at 70-85° C. for 1-2 days to obtain the nano calcium silicate hydrate seed early strength agent product, with the D50 particle size controlled at 50-100 nm; The source solution is a calcium salt solution and a silicate solution, which provide a calcium source and a silicate source for the synthesis of the nano-hydrated calcium silicate seed early strength agent. The specific composition of the source solution is a calcium salt solution of 2-5 mol / L calcium ions and a silicate solution of 2-6 mol / L silicate ions in molar concentration. The dispersed phase is deionized water. The preparation process is to directly dissolve the soluble calcium salt or silicate solute in deionized water according to the above material concentration, and stir at a speed of 300-600 r / min until the solute is completely dissolved. The soluble calcium salt solute is one or a combination of two of calcium chloride, calcium nitrate, calcium acetate, calcium bicarbonate, and calcium bromide, and the soluble silicon salt is one or a combination of two of sodium silicate, potassium silicate, sodium metasilicate, and potassium metasilicate. Among them, the microemulsions A and B are oil-in-water type microemulsions, which are a thermodynamically stable system. During the synthesis process, each droplet can act as an independent microreactor, thereby limiting the continuous growth of seed crystals and better controlling the synthesis conditions. The specific composition of the microemulsion is 20 to 40 parts of oil phase solution, 10 to 35 parts of surfactant, 4 to 8 parts of co-surfactant and 10 to 35 parts of source solution by mass. The preparation process is to add the oil phase solution, surfactant and co-surfactant into the reactor according to the above material ratio, stir and heat to 50 to 70°C at a speed of 500 to 800 r / min, and slowly add the source solution to the reactor at the same time, and the dropping time is 1 to 2 hours. , after the addition is completed, stirring is continued until a clear microemulsion is formed. The difference between microemulsions A and B is that microemulsion A uses a calcium source solution, and microemulsion B uses a silicon source solution, wherein the oil phase solution is one of cyclohexane, n-conane, and a hydrophobic deep eutectic solution, the surfactant is one of polyoxyethylene sorbitan laurate, sorbitan monooleate, nonylphenol polyoxyethylene ether, polyethylene glycol hexadecyl ether, and octylphenol polyoxyethylene ether, or a combination of two, the co-surfactant is one of n-propanol, n-butanol, n-pentanol, and hexadecyltrimethylammonium bromide, or a combination of two, and when using a hydrophobic deep eutectic solution, 10 to 20 parts of anhydrous ethanol are used instead of the surfactant and the co-surfactant; The separation comprises the following steps: centrifuging the aged microemulsion for a time of 10 to 30 minutes at a speed of 2500 to 5000 r / min, removing the supernatant after centrifugation, filtering the lower oil phase and washing with a detergent for 2 to 3 times to obtain a solid phase product, wherein the detergent is one of ethanol, dichloromethane, deionized water and acetone; Among them, the recovered oil phase solution of the microemulsion can be reused. When cyclohexane and n-conane are used as the oil phase solution to construct a surfactant microemulsion system, the oil phase solution can be directly recycled after filtration using the centrifugal separation product, and the recovery rate is above 75%. When a hydrophobic deep eutectic solution is used as the oil phase solution to construct a surfactant-free microemulsion system, the hydrophobic deep eutectic solution has the property of responding to CO2. By injecting CO2 to break the emulsification separation product, the recovered oil phase solution can restore the hydrophobicity and be reused in a N2 environment of 60-65°C, and the recovery rate is above 85%.

2. The method for preparing the nano calcium silicate hydrate seed early strength agent according to claim 1, characterized in that: The hydrophobic deep eutectic solution is prepared by mixing 4-methoxyphenol and dimethylaminocyclohexane in a ratio of 1:1 by mole, and stirring at room temperature for 30 to 90 minutes.

3. The method for preparing the nano calcium silicate hydrate seed early strength agent according to claim 1, characterized in that: The particle size D50 of the nanometer calcium silicate hydrate seed early strength agent product is controlled at 50-100 nm, the particle size range is 30-45 nm, and the particle size distribution presents a single peak distribution.

4. The method for preparing the nano calcium silicate hydrate seed early strength agent according to claim 1, characterized in that: The nanometer calcium hydrate crystal seed early strength agent product is suitable for oil well G grade cement and conventional silicate cement at an addition amount of 1-6wt%.

5. The method for preparing the nano calcium silicate hydrate seed early strength agent according to any one of claims 1 to 4, comprising the following steps: Prepare oil-in-water microemulsion systems A and B with calcium salt and silicate source solutions as internal phases, quickly mix microemulsions A and B, react and stir at a speed of 500-800 r / min for 3-6 hours, age for 12-24 hours, separate the solid product for washing, and dry it at 70-85°C in a ventilated environment for 1-2 days to obtain a high-performance nano-hydrated calcium silicate seed early strength agent.

Citation Information

Patent Citations

  • Superhard transition metal compound and preparation method thereof

    CN116535219A

  • Nano hydrated calcium silicate crystal nucleus early strength agent as well as preparation method and application thereof

    CN117209200A

  • Nanometer hydrated calcium silicate crystal nucleus early strength agent with high dispersion stability and preparation method and application thereof

    CN118420264A

Cited By

  • Nano-seed crystal early strength agent, preparation method and micro-reaction system adopted by nano-seed crystal early strength agent

    CN121060421A